PEDAGOGICAL PROBLEMS AND RECOMMENDATIONS ON SOLUTIONS OF USING THE ELEMENTS OF COMPUTER GAMES IN THE CONTEMPORARY EDUCATION (Scientific journal of the Fergana State University, 2023)
This article discusses one of the most powerful socio-psychological factors influencing the spirituality of young people - the use of computer games in the educational process. The results of social surveys and experiments are presented. Some suggestions on creating computer educational games are presented. The problems that arise in the process of creating and using pedagogical computer games are listed and the authors' recommendations are given as a solution.